Effects of Income Inequality on Aggregate Output - Brueckner, Markus (World Bank, Washington, DC, 2015)
This paper estimates the effect of income inequality on real gross domestic product per capita using a panel of 104 countries during the period 1970–2010. The empirical analysis addresses endogeneity issues by using instrumental variables estimation and controlling for country and time fixed effects. The analysis finds that, on average, income inequality has a significant negative effect on transitional gross domestic product per capita growth and the long-run level of gross domestic product per capita. However, the impact varies by the level of economic development, so much so that in poor countries income inequality has a significant positive effect on gross domestic product per capita.